Analysis of Students’ English-Speaking Ability through Media of Learning Video - Akhrif Yahsya (Journal of English Education and Linguistics, 2023)
This study aims to describe the ability of students’ fifth semester of English STAIN Mandailing Natal to speak English through learning video media in the Instructional Media for ELT (English Language Teaching) course. This research is descriptive qualitative research in which the writer describes and analyzes students' speaking abilities. The population in this study were 10 students from the fifth semester of the English Department at STAIN Mandailing Natal for the academic year of 2022-2023. Based on the results of the study it can be concluded that students' speaking abilities are between the "above average" and "excellent" levels. In other words, it can be concluded that learning videos can be an interesting alternative media that students can use to improve students' speaking ability